CONCEPT OF "FAMILY LINEAGE" AND THE IMAGE OF HOME IN LUDMILA ULITSKAYA’S NOVEL "MEDEA AND HER CHILDREN" - Siddiqjonova Durdona Sohibjon qizi (International Journal of Literature and Language Studies, 2026)
This article attempts a comprehensive analysis of the artistic structure of Ludmila Ulitskaya’s novel Medea and Her Children through the prism of the concept of "family lineage" and the multilayered image of home. The central focus of the research is the figure of Medea Sinopli, who is interpreted as a living link between the past and the future, transforming biological kinship into profound spiritual continuity. The author explores in detail how the Crimean coast and the old house become not merely geographical settings, but a sacred space ("genius loci") that stands in opposition to the historical chaos of the 20th century. The paper argues that the transformation of the ancient myth allows Ulitskaya to affirm new values of matriarchy, where the childless heroine becomes a true mother to the entire extended family, uniting different ethnicities and cultures into a single "cosmos" of lineage.